Research on the spatial structure of desert tourism flow based on ecological digital footprints: a case study of Ningxia - Dong, Baoling; Guo, Xiaowei; Luo, Qiang (Frontiers in Environmental Science, 2025)
Based on the analysis of tourists’ digital footprints from 2018 to 2022, this paper examines the desert tourism in the Upper Reaches of the Yellow River in Ningxia, China. By combining social network analysis and ArcGIS methods, it visually presents the spatial network structure characteristics of tourism flow in Ningxia’s desert destinations in recent years. The results indicate that (1) the high rate of visitors in Ningxia is closely related to the grade value of the scenic spots and the popularity of cities, and the most popular scenic spots are concentrated in the Ningxia section of the Yellow River Basin. (2) Hot desert scenic spots with historical, cultural, and urban development characteristics have greater advantages and competitiveness; these spots can better connect with less popular tourism nodes and serve as breakthrough points for the rational allocation of tourism resources. (3) The tourism flow network among scenic spots in Ningxia is relatively loose, with an imbalance in the tourism network among these spots. (4) The spatial tourism flow presents a pattern of superposition and coincidence of multiple triangular structures. Among them, Zhongwei, Yinchuan, and Shizuishan are more attractive to tourists than Wuzhong and Guyuan.